(untitled) (Proceedings of the International Conference on Hospitality and Tourism Management, 2022)
Halal tourism is currently widely applied to meet the needs of Muslim tourists and increase the interest and number of tourists to visit by several countries. This study examines the influences of halal tourism attributes and tourist’s travel experience on destination image. More specifically, this study aims to identify the role of each dimensions of halal tourism attributes and travel experience in enhancing destination image to further provide innovation on the services provided by management. Five dimensions of halal tourism attributes (social environment, facilities, food & beverages, service, and staff), four dimensions of travel experience (escapism, entertainment, esthetics, and education), and four dimensions of destination image (scenery, infrastructure, affective, and water sports) were identified from previous studies. Data were collected by distributing self-administered online questionnaire to 330 respondents who have visited Lombok in the last two years. Structural equation modelling was used to analyze the data using PLS-SEM to examine the impact of dimensions and variables that influence destination image. The results show that both halal tourism attributes (HTA) and travel experience (TE) positively influence destination image (DI), with TE has the stronger impact on DI. Partial least squares regression analysis shows that from all the dimensions of TE, entertainment and escapism have the strongest influence, while for HTA, food & beverages and facilities have biggest value in developing halal friendly attributes. Meanwhile, from all the dimensions of DI, the affective dimension shows the biggest value. The results show that tourist experience together with halal tourism factors can positively affect the destination image of Lombok. Therefore, to be able to innovate on the services provided in this tourism sector, managers can focus on developing halal friendly attributes while keep entertaining the tourists to develop positive destination image.